Career guidance in Denmark: Social control in a velvet glove - Plant, Peter (2011)
Career guidance in Denmark is well organised, highly structured, and professionalised. This mirrors the strong policy focus on the role of guidance as a soft societal steering instrument. With this backdrop, the dilemma in Danish guidance is the delicate balance between guidance as an instrument for personal development, and guidance as social control.